Industrial Development in Cities - Henderson, Vernon; Kuncoro, Ari; Turner, Matt (Journal of Political Economy, 1995)
This paper uses data for eight manufacturing industries to test for and characterize dynamic production externalities in cities. The authors find evidence of both Marshall-Arrow-Romer (MAR) externalities, which are associated with past own industry employment concentration, and Jacobs externalities, which are associated with past diversity of local total employment. For mature capital goods industries, there is evidence of MAR externalities but none of Jacobs externalities. For new high-tech industries, there is evidence of Jacobs and MAR externalities. These findings are consistent with the notion that new industries prosper in large, diverse metropolitan areas but, with maturity, production decentralizes to smaller, more specialized cities. Copyright 1995 by University of Chicago Press.